Constraints on Paleoclimate from 11.5 to 5.0 ka from Shoreline dating and Hydrologic Budget Modeling of Baqan Tso, Southwestern Tibetan Plateau. Issue 1 (January 2015) - Huth, Tyler; Hudson, Adam M.; Quade, Jay; Guoliang, Lei; Hucai, Zhang
Abstract: 14 C dating of shoreline deposits of closed-basin lake Baqan Tso in the western Tibetan Plateau shows that lake level regressed from the undated highstand (46 m above modern, 4.3 × modern surface area) of likely earliest Holocene age by 11.5 ka, and remained larger than modern until at least ≈ 5.0 ka. The shoreline record broadly matches other regional climate records, with lake level closely following Northern Hemisphere summer insolation overprinted by sub-millennial lake-level oscillations. A model coupling modern land runoff and lake surface heat closely reproduces estimated modern precipitation of ≈ 240 mm/yr. We estimate that the Baqan Tso basin required ≈ 380 mm/yr precipitation to sustain the maximum early Holocene lake area, a 55% increase over modern. Precipitation increases, not glacial meltwater, drove lake-level changes, as Baqan Tso basin was not glaciated during the Holocene. Our estimate assumes early Holocene insolation (≈ 1.3% overall increase), and mean annual increases of 2°C in temperature, and 37% in relative humidity. We additionally developed a Holocene precipitation history for Baqan Tso using dated paleolake areas. Using the modern and early Holocene model results as end-members, we estimate precipitation in the western Tibetan Plateau which was 300–380 mm/yr between 5.0 and 11.5 ka, with error of ± 29–57 mm/yr (± 12–15%).